2021
DOI: 10.3389/fphar.2021.667254
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Renin-Angiotensin-Aldosterone System in the Heart and Lung: Focus on COVID-19

Abstract: The renin-angiotensin-aldosterone system (RAAS) firstly considered as a cardiovascular circulating hormonal system, it is now accepted as a local tissue system that works synergistically or independently with the circulating one. Evidence states that tissue RAAS locally generates mediators with regulatory homeostatic functions, thus contributing, at some extent, to organ dysfunction or disease. Specifically, RAAS can be divided into the traditional RAAS pathway (or classic RAAS) mediated by angiotensin II (AII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 99 publications
(126 reference statements)
0
28
0
Order By: Relevance
“…Cardiac hypertrophy and fibrosis are common effects of this process, and they often lead to adverse ventricular remodeling [ 18 ]. Ang II is also commonly responsible for inflammatory processes and alterations in the electrophysiological properties of the heart [ 19 ].…”
Section: The Renin-angiotensin Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Cardiac hypertrophy and fibrosis are common effects of this process, and they often lead to adverse ventricular remodeling [ 18 ]. Ang II is also commonly responsible for inflammatory processes and alterations in the electrophysiological properties of the heart [ 19 ].…”
Section: The Renin-angiotensin Systemmentioning
confidence: 99%
“…The activity of various proinflammatory transcription nuclear factors (e.g., nuclear factor-kappaB (NF- κ B)) is also increased [ 21 ]. Additionally, ATI receptors cause the release of proinflammatory cytokines, such as tumor necrosis factor- α (TNF- α ) and interleukin-6 (IL-6) [ 19 ].…”
Section: The Renin-angiotensin Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…SARS-CoV-2 gains entrance to airway epithelial cells (AECs) through binding of the viral spike protein to the angiotensin-converting enzyme 2 (ACE2) on the cell surface (Hoffmann et al, 2020). However, ACE2 also converts angiotensin II into angiotensin-(1-7) and counterbalances the renin-angiotensin-aldosterone system, with resultant protective effects in the cardiovascular system (Mascolo et al, 2021). Some data suggest that two common antihypertension medications (angiotensin II receptor antagonists, ARBs; and angiotensin-convertingenzyme inhibitors, ACEIs) may increase ACE2 expression in heart and kidney cells (Tikellis et al, 2003;Ferrario et al, 2005a;Ferrario et al, 2005b;Ocaranza et al, 2006;Yang et al, 2013;Zhang et al, 2014), fueling debate early in the COVID-19 pandemic about how these widely used medications might modulate SARS-CoV-2 infectivity and the risk of In some animal studies ARBs and ACEIs were observed to increase ACE2 expression in some tissues (Tikellis et al, 2003;Ferrario et al, 2005a;Ferrario et al, 2005b;Ocaranza et al, 2006;Yang et al, 2013;Zhang et al, 2014), but the impact of these drugs on ACE2 expression in humans is mixed , and ACE2 was found to be protective against pulmonary disease from SARS-CoV in mice (Altman et al, 2017).…”
Section: Introductionmentioning
confidence: 99%